PENGARUH JENIS KELAMIN DAN LATAR BELAKANG SEKOLAH TERHADAP TOLERANSI PERBEDAAN MAZHAB FIQH - Fariz Zul Fahmi, Abbas Arfan, (Fakultas Syariah, 2011)
This quantitative research is to measure the quantity of tolerance attitude value in responding the difference tendency in affiliating school of thoughts (madzhab) among youths especially university students. This research is quantitative research which applies survey method, probability sampling-simple random sampling data collection technique, skala likert instrument and theta formula analysis technique. The result shows two main findings; 1) there is no significant relationship between sex and tolerance attitude toward school of thought affiliation among university students. However, female students are more tolerant than male students.2) there is no significant relationship between school background and tolerant attitude towards school of thought affiliation among students. by contrast, non–islamic senior high school graduates are more tolerant than those Islamic senior high school graduates. Penelitian ini berusaha mengukur secara kuantitas nilai sikap toleransi dalam menyikapi perbedaan mazhab fiqh terutama bagi generasi muda seperti mahasiswa. Jenis penelitian ini adalah kuantitatif dengan metode survey, teknik pengambilan datanya dengan probability sampling-simple random sampling, instrumen penelitiannya dengan model skala Likert dan teknik analisis datanya dengan rumus theta yang diuji dengan uji hipotesis chi-square. Hasil penelitian ini adalah (1) Tidak ada hubungan yang signifikan antara perbedaan jenis kelamin dengan sikap toleransi bermazhab fiqh mahasiswa. namun mahasiswa dengan jenis kelamin perempuan lebih toleran daripada laki-laki, (2) Tidak ada hubungan yang signifikan antara perbedaan latar belakang sekolah dengan sikap toleransi bermazhab fiqh mahasiswa. Namun mahasiswa dari latar belakang sekolah non Madrasah Aliyah (MA) lebih toleran dari yang MA.